Roles of sphingosine-1-phosphate signaling in cancer - Peng Wang; Yonghui Yuan; Wenda Lin; Hongshan Zhong; Ke Xu; Xun Qi (Cancer Cell International, 2019)
Abstract The potent pleiotropic lipid mediator sphingosine-1-phosphate (S1P) participates in numerous cellular processes, including angiogenesis and cell survival, proliferation, and migration. It is formed by one of two sphingosine kinases (SphKs), SphK1 and SphK2. These enzymes largely exert their various biological and pathophysiological actions through one of five G protein-coupled receptors (S1PR1–5), with receptor activation setting in motion various signaling cascades. Considerable evidence has been accumulated on S1P signaling and its pathogenic roles in diseases, as well as on novel modulators of S1P signaling, such as SphK inhibitors and S1P agonists and antagonists. S1P and ceramide, composed of sphingosine and a fatty acid, are reciprocal cell fate regulators, and S1P signaling plays essential roles in several diseases, including inflammation, cancer, and autoimmune disorders. Thus, targeting of S1P signaling may be one way to block the pathogenesis and may be a therapeutic target in these conditions. Increasingly strong evidence indicates a role for the S1P signaling pathway in the progression of cancer and its effects. In the present review, we discuss recent progress in our understanding of S1P and its related proteins in cancer progression. Also described is the therapeutic potential of S1P receptors and their downstream signaling cascades as targets for cancer treatment.